Implied consent and sexual assault : intimate relationships, autonomy, and voice - Plaxton, Michael, 1975- (McGill-Queen's University Press, 2015)
"In R. v. Ewanchuk, the Supreme Court of Canada held that sexual touching must be accompanied by express, contemporaneous consent. In doing so, the Court rejected the idea that sexual consent could be 'implied'. Ewanchuk was a landmark ruling, reflecting a powerful commitment to women's equality and sexual autonomy. In articulating limits on the circumstances under which women can be said to 'consent' to sexual touching, however, the decision also restricts their autonomy--specifically, by denying them a voice in determining the norms that should govern their intimate relationships and sexual lives. In Implied Consent and Sexual Assault, Michael Plaxton argues that women should have the autonomy to decide whether, and under what circumstances, sexual touching can be appropriate in the absence of express consent. Though we should exercise caution before resurrecting a limited doctrine of implied consent in the sexual sphere, there are reasons to think that sexual assault law could accommodate it without undermining the sexual autonomy or equality rights of women. In reaching this conclusion, Plaxton challenges widespread beliefs about autonomy, consent, and the objectives underpinning the offence of sexual assault in Canada. Drawing upon a range of contemporary criminal law theorists and feminist scholars, Implied Consent and Sexual Assault reconsiders the nature of mutuality in a world dominated by gender norms, the proper scope of criminal law, and the true meaning of sexual autonomy."--